T-Align, a web-based tool for comparison of multiple terminal restriction fragment length polymorphism profiles - Smith, Cindy J.; Danilowicz, Bret S.; Clear, Adrian K.; Costello, Fintan J.; Wilson, Bryan; Meijer, Wim G. (FEMS microbiology ecology, 2005)
Terminal restriction fragment length polymorphism (tRFLP) is a potentially high-throughput method for the analysis of complex microbial communities. Comparison of multiple tRFLP profiles to identify shared and unique components of microbial communities however, is done manually, which is both time consuming and error prone. This paper describes a freely accessible web-based program, T-Align ( http://inismor.ucd.ie/~talign/), which addresses this problem. Initially replicate profiles are compared and used to generate a single consensus profile containing only terminal restriction fragments that occur in all replicate profiles. Subsequently consensus profiles representing different communities are compared to produce a list showing whether a terminal restriction fragment (TRF) is present in a particular sample and its relative fluorescence intensity. The use of T-Align thus allows rapid comparison of numerous tRFLP profiles. T-Align is demonstrated by alignment of tRFLP profiles generated from bacterioplankton communities collected from the Irish and Celtic Seas in November 2000. Ubiquitous TRFs and site-specific TRFs were identified using T-Align.